PERBEDAAN TEKANAN DARAH PERAWAT SEBELUM DAN SETELAH DINAS PAGI, SORE, DAN MALAM DIRUANG INTENSIVE CARE UNITRSUP. DR. M. DJAMIL PADANG - Yesi Fadriyanti, Nova Yanti, (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Blood pressure is influenced by age, stress, ethnicity, gender, daily variation, medications, activity andweight, as well as smoking. Nurses at risk of heart disease, hypertension, thyroid, asthma, digestivedisorders, and diabetes as the effects of shift work. The research design was quasi experiment aimed tocompare the blood pressure of nurses before and after shifts, morning, afternoon, and evening. Sampleof 36 nurses who work shifts in the intensive care units. The results showed a significant differencebetween systolic before and after the evening shift (p = 0, 17). Furthermore, there is no significantdifference between the systolic (p = 0.781) and diastolic (p = 0.248) before and after the morning shift,diastolic (p = 0.558) before and after the afternoon shift, and systolic (p = 0.379) and diastolic (p =0.649) before and after the night shift. Nurses have risk factors for obesity increased blood pressure,rarely exercise and work shifts. This study recommends that nurses manage their weight, exercisingregularly, and reducing stress to avoid a rise in blood pressure, as well as further research to designRandomized Controlled Trial (RCT) with a number of larger samplesKeywords: Blood pressure, shift, nurse